Nuclear Factor-kappaB in Autoimmunity: Man and Mouse - Bahar Miraghazadeh; Bahar Miraghazadeh; Matthew C. Cook; Matthew C. Cook; Matthew C. Cook (Frontiers in Immunology, 2018)
NF-κB (nuclear factor-kappa B) is a transcription complex crucial for host defense mediated by innate and adaptive immunity, where canonical NF-κB signaling, mediated by nuclear translocation of RelA, c-Rel, and p50, is important for immune cell activation, differentiation, and survival. Non-canonical signaling mediated by nuclear translocation of p52 and RelB contributes to lymphocyte maturation and survival and is also crucial for lymphoid organogenesis. We outline NF-κB signaling and regulation, then summarize important molecular contributions of NF-κB to mechanisms of self-tolerance. We relate these mechanisms to autoimmune phenotypes described in what is now a substantial catalog of immune defects conferred by mutations in NF-κB pathways in mouse models. Finally, we describe Mendelian autoimmune syndromes arising from human NF-κB mutations, and speculate on implications for understanding sporadic autoimmune disease.